Jenis - Jenis Udang Air Tawar di Sungai Bedog Kabupaten Bantul - Suwartiningsih, Nurul; Pertiwi, Dyah Ayu Indah; Budiantoro, Agung (Jurnal Riset Daerah, 2020)
Bedog River is one of the rivers that passes through Bantul Regency and has biological resources, one of which is freshwater shrimp. The purpose of this study was to determine the types and potential of freshwater shrimp found in the Bedog River, Bantul Regency, and knowing whether the environmental parameters in the Bedog river are in accordance with the ideal conditions for the growth of freshwater shrimp. The research location was determined by purposive sampling method at three stations (ST), each station made three sampling points. In addition, environmental parameters were also measured including temperature, pH, salinity, river flow velocity, dissolved CO2, and DO. Data analysis was carried out descriptively by comparing the morphological characters of each type of freshwater shrimp. The data obtained are presented in tables and diagrams. The results of the study found four species of shrimp Macrobrachium sintangense, Macrobrachium equidens, Caridina sp. and Caridina elongapoda with a total of 116 individuals. The potential of each type of freshwater shrimp found in the Bedog River is for consumption and ornamental pets. Macrobrachium equidens, M. sintangense, and C. elongapoda have the potential to be consumed, while Caridina sp. potential as ornamental shrimp. Environmental parameters that are in accordance with ideal conditions for the growth of freshwater shrimp in the Bedog River are found at stations I and III, while at station II are less suitable for ideal conditions for shrimp growth because the river is polluted by industrial waste so that the water quality decreases.